Artificial Intelligence in Microfinance: Enhancing Customer Experience at ESAF Bank - Cherian, Aiswarya; T.T, Arun Kumar. (NPRC Journal of Multidisciplinary Research, 2025)
Artificial Intelligence (AI) is revolutionizing the microfinance sector by enhancing customer experience, streamlining operations, and improving financial inclusion. ESAF Bank, a leading microfinance institution in India, has embraced AI-driven solutions to optimize its service delivery and meet the evolving needs of its customers. This study explores how AI technologies such as chatbots, predictive analytics, and automated credit scoring have transformed ESAF Bank's operations, leading to better customer engagement, personalized financial solutions, and improved risk management. The research highlights the challenges faced in AI adoption, including data security concerns, regulatory compliance, and digital literacy among customers. Findings from this study provide insights into the strategic implementation of AI in microfinance and its potential to drive sustainable growth and financial empowerment for underserved communities.